Demystifying the Relationship Between Metformin, AMPK, and Doxorubicin Cardiotoxicity - Singh, Manrose; Nicol, Akito T.; DelPozzo, Jaclyn; Wei, Jia; Singh, Mandeep; Nguyen, Tony; Kobayashi, Satoru; Liang, Qiangrong (Frontiers in Cardiovascular Medicine, 2022)
Doxorubicin (DOX) is an extremely effective and wide-spectrum anticancer drug, but its long-term use can lead to heart failure, which presents a serious problem to millions of cancer survivors who have been treated with DOX. Thus, identifying agents that can reduce DOX cardiotoxicity and concurrently enhance its antitumor efficacy would be of great clinical value. In this respect, the classical antidiabetic drug metformin (MET) has stood out, appearing to have both antitumor and cardioprotective properties. MET is proposed to achieve these beneficial effects through the activation of AMP-activated protein kinase (AMPK), an essential regulator of mitochondrial homeostasis and energy metabolism. AMPK itself has been shown to protect the heart and modulate tumor growth under certain conditions. However, the role and mechanism of the hypothesized MET-AMPK axis in DOX cardiotoxicity and antitumor efficacy remain to be firmly established by in vivo studies using tumor-bearing animal models and large-scale prospective clinical trials. This review summarizes currently available literature for or against a role of AMPK in MET-mediated protection against DOX cardiotoxicity. It also highlights the emerging evidence suggesting distinct roles of the AMPK subunit isoforms in mediating the functions of unique AMPK holoenzymes composed of different combinations of isoforms. Moreover, the review provides a perspective regarding future studies that may help fully elucidate the relationship between MET, AMPK and DOX cardiotoxicity.